Taxonomic study of leafhopper genera Balala and Kalasha (Hemiptera: Cicadellidae: Hylicinae) with three new species, and a new name to replace the homonym Imbricatala Zhang & Tang - Zou, Hongfen; Cao, Yanghui; Zhang, Yalin (Zootaxa, 2026)
Two leafhopper genera of the tribe Sudrini, Balala Distant and Kalasha Distant, are reviewed and three new species are described and illustrated: Balala brachyprocessa, B. mediodentata and Kalasha anisodenta spp. nov. A new name, Imbrexala nom. nov., is proposed here to replace the homonym Imbricatala Zhang & Tang, hom. nov. with two new combinations.